Diatom Epipelik sebagai Bioindikator Pencemaran di Estuari Suwung - Yesie Rahayu Ananingtyas; I Gede Hendrawan; Yulianto Suteja (Fakultas Kelautan dan Perikanan Universitas Udayana, 2018)
Epiphelic diatoms are the living diatoms adhere to the bottom substrate of the waters. Epiphelic diatoms ware used as bioindicators because sensivity of enviromental change, widely distributed, and ware not affected by currents. Epiphelic diatom research as a bioindicator of pollution in the Suwung estuary was conducted in December 2016 and January 2017. The sampling of epiphelic diatom using the method of